Create MEME generator app in Android Studio : learn to create the popular MEME generator app for Android - Radev, Tihomir (Apress, 2023)
MEMEs are popular images with captions and are often shared repeatedly on social platforms. A MEME generator app is a fun and popular and popular tool, particularly amongst young people. This video will show you how to create and use a simple version of it. The app will have a basic gallery with example images, labels for the captions, and a button for the save. In this video you'll learn how to build your own MEME Generator app for Android. The app allows users to add custom images and create custom captions for it so it can became a MEME. Then they will be able to save the MEME in the Android gallery app on the device and share it later on social platforms. What You'll Learn How to create simple gallery with images using RecyclerView. How to transition to another screen and pass the image to the other view. How to design the text elements, images and buttons and arrange them on the screen. How to screenshot a view from the app and save it as image in the device. Who This Video Is For People with more advanced skills in Android Studio and Java are targeted but the video will be useful for total beginners as well.